Pengaruh Penggunaan Game Edukasi Interaktif Wordwall terhadap Peningkatan Pemahaman Konsep Pembelajaran Bahasa Indonesia di SD - Amelia Meliana Wila; Meisyani Jedrina Gunawan; Elfarretha Justi Liana Taopan; Kesya Renata Ndun; Elisabet Tenis (ARZUSIN, 2026)
This study was conducted in response to the still limited number of studies examining the use of Wordwall as an interactive educational game medium to support elementary school students’ understanding of Indonesian language concepts, despite the important role of digital learning technologies in improving the quality of learning processes in the modern era. The study aimed to analyze the effect of using Wordwall on improving students’ understanding of Indonesian language concepts. A quantitative approach was employed with a pre-experimental one-group pretest–posttest design. The research subjects were 15 grade IIIA students selected using a total sampling technique, with pretest and posttest instruments each consisting of 20 items. The collected data were analyzed using normality and homogeneity tests, t-tests, and n-gain score calculations with the assistance of SPSS version 16. The results showed that the data met the assumptions of normality and homogeneity, and the t-test produced a significance value of 0.00 < 0.05, indicating a significant effect of Wordwall use on students’ understanding of Indonesian language concepts. The average student learning outcomes increased from 58.33 to 81.67, with the n-gain categorized as moderately effective. These findings confirm that Wordwall can serve as an instructional medium that more optimally enhances students’ conceptual understanding and opens up opportunities for further research with larger samples and stronger experimental designs to strengthen the theoretical basis for the effectiveness of digital educational media and to generate practical recommendations for teachers.